2008
DOI: 10.1016/j.modgep.2007.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Expression and functional analysis of a novel Fusion Competent Myoblast specific GAL4 driver

Abstract: In the Drosophila embryo, body wall muscles are formed by the fusion of two cell types, Founder Cells (FCs) and Fusion Competent Myoblasts (FCMs). Using an enhancer derived from the Dmef2 gene ([C/D]*), we report the first GAL4 driver specifically expressed in FCMs. We have determined that this GAL4 driver causes expression in a subset of FCMs and, upon fusion, in developing myotubes from stage 14 onwards. In addition, we have shown that using this Dmef2-5x[C/D]*-GAL4 driver to express dominant negative Rac in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…To investigate which activities, besides JAK/STAT signaling, are required in the muscles for the immune responses against wasp infection, we individually suppressed several well-known immune-related signaling pathways, including the p38, c-Jun N-terminal kinase (JNK), Toll, and insulin signaling pathways. We suppressed these pathways by expressing either RNA interference or dominant-negative constructs with a muscle-specific driver 34 , Mef2-GAL4 , and then assayed encapsulation rates and hemocyte numbers. We found that suppression of insulin signaling in the muscles, by expressing InR RNAi or InR DN , significantly reduced the encapsulation rate (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate which activities, besides JAK/STAT signaling, are required in the muscles for the immune responses against wasp infection, we individually suppressed several well-known immune-related signaling pathways, including the p38, c-Jun N-terminal kinase (JNK), Toll, and insulin signaling pathways. We suppressed these pathways by expressing either RNA interference or dominant-negative constructs with a muscle-specific driver 34 , Mef2-GAL4 , and then assayed encapsulation rates and hemocyte numbers. We found that suppression of insulin signaling in the muscles, by expressing InR RNAi or InR DN , significantly reduced the encapsulation rate (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To directly investigate the role of muscle JAK/STAT signaling in the immune response, we suppressed individual components of this pathway in larval somatic muscles by expressing dominant‐negative constructs of either the cytokine receptor gene domeless ( dome DN ) or the single Drosophila STAT gene Stat92E ( Stat92E DN ), with the Mef2‐GAL4 muscle‐specific driver . This driver is expressed in larval muscles, but not for instance in fat body (Appendix Fig S3A, C and D).…”
Section: Resultsmentioning
confidence: 99%
“…The myoblast fusion is asymmetric and takes place between FCs and FCMs. Previous reports (Estrada et al, 2006; Beckett and Baylies, 2007; Beckett et al, 2008) were at the origin of a hypothesis that FCMs are not “naïve” myoblasts and contribute to the modulation of fusion process. In contrast, our results support a view that FCs rather than FCMs carry the instructive information and allow us to conclude that FCMs do not play an active role in setting the number of fusion events.…”
Section: Discussionmentioning
confidence: 99%